UPAYA MENINGKATKAN NUMERASI SISWA UPTD SMP NEGERI 6 KUPANG TENGAH DENGAN METODE HITUNG CEPAT - Bukifan, Kristina Yusria; Elie, Melkysedek; Nekleu, Ermalinda; Fahik, Julianti Putri; Djong, Kristoforus Djawa (Universitas Batanghari Jambi, 2026)
This study seeks to enhance the computational abilities of students at UPTD SMP Negeri 6 Kupang Tengah via the use of the quick calculation technique. The students' preliminary numeracy abilities remain deficient, as shown by the pre-test results, which show scores between 40 and 70, with a class average of 58%. Students struggle with fundamental arithmetic operations and the resolution of contextual difficulties. This study used a qualitative descriptive methodology, with 10 students as participants. The intervention was conducted using microlearning activities, quick calculation exercises, numerical games, and individualized tuition over a period of roughly two months. The post-test findings indicated a substantial improvement, with student scores ranging from 76 to 91 and the class average rising to 84.6%. All pupils attained mastery of the learning goals. This discovery indicates that the quick calculation approach enhances pupils' comprehension of numerical patterns, precision, and calculation speed. This approach has shown applicability in schools with constrained resources. The quick calculation approach serves as an alternate learning strategy both straightforward and efficacious for enhancing pupils' calculating abilities.